High-content and super-resolution microscopy reveals the dynamic nuclear architecture and mobile epigenetic marks in Plasmodium falciparum - Birkholtz, Lyn-Marie (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.